Effect of ARYA Programme in Employment and Income Generation of the Rural Youths - Sahoo, Madhusmita; Acharya, Sumita; Nayak, Ambika Prasad; Sethy, Sonitarani (Indian Journal of Extension Education, 2023)
Rural youths are the future of India’s progress in agriculture. In order to keep the interest of youths in agriculture and maintain their sustainable livelihoods, ICAR through its Agricultural Extension division has implemented Attracting and Retaining Youth in Agriculture (ARYA) programme through different identified KVKs in the country. Five KVKs from Odisha have been implementing this programme, out of which present research carried out in the Puri KVK in the year 2022, where the ARYA project has been focusing on four enterprises i.e., mushroom, poultry, apiary, fish production including fish seed with a total of 174 rural youths. After the implementation of ARYA, among the five enterprises promoted under ARYA, the performance of the mushroom enterprise gave the highest net income and highest average production. On the other hand benefit cost ratio was higher in fishery enterprises. Various economic performance indicators showed a positive and significant relation with the social profile of the rural youths. The implementation of programme brought the convergence of several institutions to render technical support to rural youth.
Keywords: Apiary; ARYA; Fish production; Income generation; Mushroom; Poultry; Rural youths; Sustainable livelihood